Measurement of e+e- momentum and angular distributions from linearly polarized photon collisions - STAR Collaboration (Physical Review Letters, 2021)
The Breit-Wheeler process which produces matter and antimatter from photon collisions is experimentally investigated through the observation of 6085 exclusive electron-positron pairs in ultraperipheral Au+Au collisions at sqrt[s_{NN}]=200 GeV. The measurements reveal a large fourth-order angular modulation of cos4DELTAphi=(16.8+/-2.5)% and smooth invariant mass distribution absent of vector mesons (phi, omega, and rho) at the experimental limit of <=0.2% of the observed yields. The differential cross section as a function of e{+}e{-} pair transverse momentum P_{} peaks at low value with sqrt[ ]=38.1+/-0.9 MeV and displays a significant centrality dependence. These features are consistent with QED calculations for the collision of linearly polarized photons quantized from the extremely strong electromagnetic fields generated by the highly charged Au nuclei at ultrarelativistic speed. The experimental results have implications for vacuum birefringence and for mapping the magnetic field which is important for emergent QCD phenomena.
54 citations (Crossref) [2023-10-31] Place: United States Adam, J. Brookhaven National Laboratory, Upton, New York 11973. Adamczyk, L. AGH University of Science and Technology, FPACS, Cracow 30-059, Poland. Adams, J R. Ohio State University, Columbus, Ohio 43210. Adkins, J K. University of Kentucky, Lexington, Kentucky 40506-0055. Agakishiev, G. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Aggarwal, M M. Panjab University, Chandigarh 160014, India. Ahammed, Z. Variable Energy Cyclotron Centre, Kolkata 700064, India. Alekseev, I. Alikhanov Institute for Theoretical and Experimental Physics NRC "Kurchatov Institute," Moscow 117218, Russia. Alekseev, I. National Research Nuclear University MEPhI, Moscow 115409, Russia. Anderson, D M. Texas A&M University, College Station, Texas 77843. Aparin, A. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Aschenauer, E C. Brookhaven National Laboratory, Upton, New York 11973. Ashraf, M U. Central China Normal University, Wuhan, Hubei 430079. Atetalla, F G. Kent State University, Kent, Ohio 44242. Attri, A. Panjab University, Chandigarh 160014, India. Averichev, G S. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Bairathi, V. Indian Institute of Science Education and Research (IISER), Berhampur 760010, India. Barish, K. University of California, Riverside, California 92521. Behera, A. State University of New York, Stony Brook, New York 11794. Bellwied, R. University of Houston, Houston, Texas 77204. Bhasin, A. University of Jammu, Jammu 180001, India. Bielcik, J. Czech Technical University in Prague, FNSPE, Prague 115 19, Czech Republic. Bielcikova, J. Nuclear Physics Institute of the CAS, Rez 250 68, Czech Republic. Bland, L C. Brookhaven National Laboratory, Upton, New York 11973. Bordyuzhin, I G. Alikhanov Institute for Theoretical and Experimental Physics NRC "Kurchatov Institute," Moscow 117218, Russia. Brandenburg, J D. Brookhaven National Laboratory, Upton, New York 11973. Brandenburg, J D. Shandong University, Qingdao, Shandong 266237. Brandin, A V. National Research Nuclear University MEPhI, Moscow 115409, Russia. Butterworth, J. Rice University, Houston, Texas 77251. Caines, H. Yale University, New Haven, Connecticut 06520. Calderon de la Barca Sanchez, M. University of California, Davis, California 95616. Cebra, D. University of California, Davis, California 95616. Chakaberia, I. Brookhaven National Laboratory, Upton, New York 11973. Chakaberia, I. Kent State University, Kent, Ohio 44242. Chaloupka, P. Czech Technical University in Prague, FNSPE, Prague 115 19, Czech Republic. Chan, B K. University of California, Los Angeles, California 90095. Chang, F-H. National Cheng Kung University, Tainan 70101. Chang, Z. Brookhaven National Laboratory, Upton, New York 11973. Chankova-Bunzarova, N. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Chatterjee, A. Central China Normal University, Wuhan, Hubei 430079. Chen, D. University of California, Riverside, California 92521. Chen, J H. Fudan University, Shanghai 200433. Chen, X. University of Science and Technology of China, Hefei, Anhui 230026. Chen, Z. Shandong University, Qingdao, Shandong 266237. Cheng, J. Tsinghua University, Beijing 100084. Cherney, M. Creighton University, Omaha, Nebraska 68178. Chevalier, M. University of California, Riverside, California 92521. Choudhury, S. Fudan University, Shanghai 200433. Christie, W. Brookhaven National Laboratory, Upton, New York 11973. Crawford, H J. University of California, Berkeley, California 94720. Csanad, M. ELTE Eotvos Lorand University, Budapest H-1117, Hungary. Daugherity, M. Abilene Christian University, Abilene, Texas 79699. Dedovich, T G. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Deppner, I M. University of Heidelberg, Heidelberg 69120, Germany. Derevschikov, A A. NRC "Kurchatov Institute", Institute of High Energy Physics, Protvino 142281, Russia. Didenko, L. Brookhaven National Laboratory, Upton, New York 11973. Dong, X. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Drachenberg, J L. Abilene Christian University, Abilene, Texas 79699. Dunlop, J C. Brookhaven National Laboratory, Upton, New York 11973. Edmonds, T. Purdue University, West Lafayette, Indiana 47907. Elsey, N. Wayne State University, Detroit, Michigan 48201. Engelage, J. University of California, Berkeley, California 94720. Eppley, G. Rice University, Houston, Texas 77251. Esha, R. State University of New York, Stony Brook, New York 11794. Esumi, S. University of Tsukuba, Tsukuba, Ibaraki 305-8571, Japan. Evdokimov, O. University of Illinois at Chicago, Chicago, Illinois 60607. Ewigleben, A. Lehigh University, Bethlehem, Pennsylvania 18015. Eyser, O. Brookhaven National Laboratory, Upton, New York 11973. Fatemi, R. University of Kentucky, Lexington, Kentucky 40506-0055. Fazio, S. Brookhaven National Laboratory, Upton, New York 11973. Federic, P. Nuclear Physics Institute of the CAS, Rez 250 68, Czech Republic. Fedorisin, J. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Feng, C J. National Cheng Kung University, Tainan 70101. Feng, Y. Purdue University, West Lafayette, Indiana 47907. Filip, P. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Finch, E. Southern Connecticut State University, New Haven, Connecticut 06515. Fisyak, Y. Brookhaven National Laboratory, Upton, New York 11973. Francisco, A. Yale University, New Haven, Connecticut 06520. Fulek, L. AGH University of Science and Technology, FPACS, Cracow 30-059, Poland. Gagliardi, C A. Texas A&M University, College Station, Texas 77843. Galatyuk, T. Technische Universitat Darmstadt, Darmstadt 64289, Germany. Geurts, F. Rice University, Houston, Texas 77251. Gibson, A. Valparaiso University, Valparaiso, Indiana 46383. Gopal, K. Indian Institute of Science Education and Research (IISER) Tirupati, Tirupati 517507, India. Grosnick, D. Valparaiso University, Valparaiso, Indiana 46383. Hamad, A I. Kent State University, Kent, Ohio 44242. Hamed, A. American University of Cairo, New Cairo, New Cairo 11835, Egypt. Harris, J W. Yale University, New Haven, Connecticut 06520. He, S. Central China Normal University, Wuhan, Hubei 430079. He, W. Fudan University, Shanghai 200433. He, X. Institute of Modern Physics, Chinese Academy of Sciences, Lanzhou, Gansu 730000. Heppelmann, S. University of California, Davis, California 95616. Heppelmann, S. Pennsylvania State University, University Park, Pennsylvania 16802. Herrmann, N. University of Heidelberg, Heidelberg 69120, Germany. Hoffman, E. University of Houston, Houston, Texas 77204. Holub, L. Czech Technical University in Prague, FNSPE, Prague 115 19, Czech Republic. Hong, Y. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Horvat, S. Yale University, New Haven, Connecticut 06520. Hu, Y. Fudan University, Shanghai 200433. Huang, H Z. University of California, Los Angeles, California 90095. Huang, S L. State University of New York, Stony Brook, New York 11794. Huang, T. National Cheng Kung University, Tainan 70101. Huang, X. Tsinghua University, Beijing 100084. Humanic, T J. Ohio State University, Columbus, Ohio 43210. Huo, P. State University of New York, Stony Brook, New York 11794. Igo, G. University of California, Los Angeles, California 90095. Isenhower, D. Abilene Christian University, Abilene, Texas 79699. Jacobs, W W. Indiana University, Bloomington, Indiana 47408. Jena, C. Indian Institute of Science Education and Research (IISER) Tirupati, Tirupati 517507, India. Jentsch, A. Brookhaven National Laboratory, Upton, New York 11973. Ji, Y. University of Science and Technology of China, Hefei, Anhui 230026. Jia, J. Brookhaven National Laboratory, Upton, New York 11973. Jia, J. State University of New York, Stony Brook, New York 11794. Jiang, K. University of Science and Technology of China, Hefei, Anhui 230026. Jowzaee, S. Wayne State University, Detroit, Michigan 48201. Ju, X. University of Science and Technology of China, Hefei, Anhui 230026. Judd, E G. University of California, Berkeley, California 94720. Kabana, S. Kent State University, Kent, Ohio 44242. Kabir, M L. University of California, Riverside, California 92521. Kagamaster, S. Lehigh University, Bethlehem, Pennsylvania 18015. Kalinkin, D. Indiana University, Bloomington, Indiana 47408. Kang, K. Tsinghua University, Beijing 100084. Kapukchyan, D. University of California, Riverside, California 92521. Kauder, K. Brookhaven National Laboratory, Upton, New York 11973. Ke, H W. Brookhaven National Laboratory, Upton, New York 11973. Keane, D. Kent State University, Kent, Ohio 44242. Kechechyan, A. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Kelsey, M. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Khyzhniak, Y V. National Research Nuclear University MEPhI, Moscow 115409, Russia. Kikola, D P. Warsaw University of Technology, Warsaw 00-661, Poland. Kim, C. University of California, Riverside, California 92521. Kimelman, B. University of California, Davis, California 95616. Kincses, D. ELTE Eotvos Lorand University, Budapest H-1117, Hungary. Kinghorn, T A. University of California, Davis, California 95616. Kisel, I. Frankfurt Institute for Advanced Studies FIAS, Frankfurt 60438, Germany. Kiselev, A. Brookhaven National Laboratory, Upton, New York 11973. Kisiel, A. Warsaw University of Technology, Warsaw 00-661, Poland. Klein, S R. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Kocan, M. Czech Technical University in Prague, FNSPE, Prague 115 19, Czech Republic. Kochenda, L. National Research Nuclear University MEPhI, Moscow 115409, Russia. Kosarzewski, L K. Czech Technical University in Prague, FNSPE, Prague 115 19, Czech Republic. Kramarik, L. Czech Technical University in Prague, FNSPE, Prague 115 19, Czech Republic. Kravtsov, P. National Research Nuclear University MEPhI, Moscow 115409, Russia. Krueger, K. Argonne National Laboratory, Argonne, Illinois 60439. Kulathunga Mudiyanselage, N. University of Houston, Houston, Texas 77204. Kumar, L. Panjab University, Chandigarh 160014, India. Kunnawalkam Elayavalli, R. Wayne State University, Detroit, Michigan 48201. Kwasizur, J H. Indiana University, Bloomington, Indiana 47408. Lacey, R. State University of New York, Stony Brook, New York 11794. Lan, S. Central China Normal University, Wuhan, Hubei 430079. Landgraf, J M. Brookhaven National Laboratory, Upton, New York 11973. Lauret, J. Brookhaven National Laboratory, Upton, New York 11973. Lebedev, A. Brookhaven National Laboratory, Upton, New York 11973. Lednicky, R. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Lee, J H. Brookhaven National Laboratory, Upton, New York 11973. Leung, Y H. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Li, C. University of Science and Technology of China, Hefei, Anhui 230026. Li, W. Rice University, Houston, Texas 77251. Li, W. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Li, X. University of Science and Technology of China, Hefei, Anhui 230026. Li, Y. Tsinghua University, Beijing 100084. Liang, Y. Kent State University, Kent, Ohio 44242. Licenik, R. Nuclear Physics Institute of the CAS, Rez 250 68, Czech Republic. Lin, T. Texas A&M University, College Station, Texas 77843. Lin, Y. Central China Normal University, Wuhan, Hubei 430079. Lisa, M A. Ohio State University, Columbus, Ohio 43210. Liu, F. Central China Normal University, Wuhan, Hubei 430079. Liu, H. Indiana University, Bloomington, Indiana 47408. Liu, P. State University of New York, Stony Brook, New York 11794. Liu, P. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Liu, T. Yale University, New Haven, Connecticut 06520. Liu, X. Ohio State University, Columbus, Ohio 43210. Liu, Y. Texas A&M University, College Station, Texas 77843. Liu, Z. University of Science and Technology of China, Hefei, Anhui 230026. Ljubicic, T. Brookhaven National Laboratory, Upton, New York 11973. Llope, W J. Wayne State University, Detroit, Michigan 48201. Longacre, R S. Brookhaven National Laboratory, Upton, New York 11973. Lukow, N S. Temple University, Philadelphia, Pennsylvania 19122. Luo, S. University of Illinois at Chicago, Chicago, Illinois 60607. Luo, X. Central China Normal University, Wuhan, Hubei 430079. Ma, G L. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Ma, L. Fudan University, Shanghai 200433. Ma, R. Brookhaven National Laboratory, Upton, New York 11973. Ma, Y G. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Magdy, N. University of Illinois at Chicago, Chicago, Illinois 60607. Majka, R. Yale University, New Haven, Connecticut 06520. Mallick, D. National Institute of Science Education and Research, HBNI, Jatni 752050, India. Margetis, S. Kent State University, Kent, Ohio 44242. Markert, C. University of Texas, Austin, Texas 78712. Matis, H S. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Mazer, J A. Rutgers University, Piscataway, New Jersey 08854. Minaev, N G. NRC "Kurchatov Institute", Institute of High Energy Physics, Protvino 142281, Russia. Mioduszewski, S. Texas A&M University, College Station, Texas 77843. Mohanty, B. National Institute of Science Education and Research, HBNI, Jatni 752050, India. Mooney, I. Wayne State University, Detroit, Michigan 48201. Moravcova, Z. Czech Technical University in Prague, FNSPE, Prague 115 19, Czech Republic. Morozov, D A. NRC "Kurchatov Institute", Institute of High Energy Physics, Protvino 142281, Russia. Nagy, M. ELTE Eotvos Lorand University, Budapest H-1117, Hungary. Nam, J D. Temple University, Philadelphia, Pennsylvania 19122. Nasim, Md. Indian Institute of Science Education and Research (IISER), Berhampur 760010, India. Nayak, K. Central China Normal University, Wuhan, Hubei 430079. Neff, D. University of California, Los Angeles, California 90095. Nelson, J M. University of California, Berkeley, California 94720. Nemes, D B. Yale University, New Haven, Connecticut 06520. Nie, M. Shandong University, Qingdao, Shandong 266237. Nigmatkulov, G. National Research Nuclear University MEPhI, Moscow 115409, Russia. Niida, T. University of Tsukuba, Tsukuba, Ibaraki 305-8571, Japan. Nogach, L V. NRC "Kurchatov Institute", Institute of High Energy Physics, Protvino 142281, Russia. Nonaka, T. Central China Normal University, Wuhan, Hubei 430079. Odyniec, G. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Ogawa, A. Brookhaven National Laboratory, Upton, New York 11973. Oh, S. Yale University, New Haven, Connecticut 06520. Okorokov, V A. National Research Nuclear University MEPhI, Moscow 115409, Russia. Page, B S. Brookhaven National Laboratory, Upton, New York 11973. Pak, R. Brookhaven National Laboratory, Upton, New York 11973. Pandav, A. National Institute of Science Education and Research, HBNI, Jatni 752050, India. Panebratsev, Y. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Pawlik, B. AGH University of Science and Technology, FPACS, Cracow 30-059, Poland. Pawlik, B. Institute of Nuclear Physics PAN, Cracow 31-342, Poland. Pawlowska, D. Warsaw University of Technology, Warsaw 00-661, Poland. Pei, H. Central China Normal University, Wuhan, Hubei 430079. Perkins, C. University of California, Berkeley, California 94720. Pinsky, L. University of Houston, Houston, Texas 77204. Pinter, R L. ELTE Eotvos Lorand University, Budapest H-1117, Hungary. Pluta, J. Warsaw University of Technology, Warsaw 00-661, Poland. Porter, J. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Posik, M. Temple University, Philadelphia, Pennsylvania 19122. Pruthi, N K. Panjab University, Chandigarh 160014, India. Przybycien, M. AGH University of Science and Technology, FPACS, Cracow 30-059, Poland. Putschke, J. Wayne State University, Detroit, Michigan 48201. Qiu, H. Institute of Modern Physics, Chinese Academy of Sciences, Lanzhou, Gansu 730000. Quintero, A. Temple University, Philadelphia, Pennsylvania 19122. Radhakrishnan, S K. Kent State University, Kent, Ohio 44242. Ramachandran, S. University of Kentucky, Lexington, Kentucky 40506-0055. Ray, R L. University of Texas, Austin, Texas 78712. Reed, R. Lehigh University, Bethlehem, Pennsylvania 18015. Ritter, H G. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Roberts, J B. Rice University, Houston, Texas 77251. Rogachevskiy, O V. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Romero, J L. University of California, Davis, California 95616. Ruan, L. Brookhaven National Laboratory, Upton, New York 11973. Rusnak, J. Nuclear Physics Institute of the CAS, Rez 250 68, Czech Republic. Sahoo, N R. Shandong University, Qingdao, Shandong 266237. Sako, H. University of Tsukuba, Tsukuba, Ibaraki 305-8571, Japan. Salur, S. Rutgers University, Piscataway, New Jersey 08854. Sandweiss, J. Yale University, New Haven, Connecticut 06520. Sato, S. University of Tsukuba, Tsukuba, Ibaraki 305-8571, Japan. Schmidke, W B. Brookhaven National Laboratory, Upton, New York 11973. Schmitz, N. Max-Planck-Institut fur Physik, Munich 80805, Germany. Schweid, B R. State University of New York, Stony Brook, New York 11794. Seck, F. Technische Universitat Darmstadt, Darmstadt 64289, Germany. Seger, J. Creighton University, Omaha, Nebraska 68178. Sergeeva, M. University of California, Los Angeles, California 90095. Seto, R. University of California, Riverside, California 92521. Seyboth, P. Max-Planck-Institut fur Physik, Munich 80805, Germany. Shah, N. Indian Institute Technology, Patna, Bihar 801106, India. Shahaliev, E. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Shanmuganathan, P V. Brookhaven National Laboratory, Upton, New York 11973. Shao, M. University of Science and Technology of China, Hefei, Anhui 230026. Shen, F. Shandong University, Qingdao, Shandong 266237. Shen, W Q. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Shi, S S. Central China Normal University, Wuhan, Hubei 430079. Shou, Q Y. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Sichtermann, E P. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Sikora, R. AGH University of Science and Technology, FPACS, Cracow 30-059, Poland. Simko, M. Nuclear Physics Institute of the CAS, Rez 250 68, Czech Republic. Singh, J. Panjab University, Chandigarh 160014, India. Singha, S. Institute of Modern Physics, Chinese Academy of Sciences, Lanzhou, Gansu 730000. Smirnov, N. Yale University, New Haven, Connecticut 06520. Solyst, W. Indiana University, Bloomington, Indiana 47408. Sorensen, P. Brookhaven National Laboratory, Upton, New York 11973. Spinka, H M. Argonne National Laboratory, Argonne, Illinois 60439. Srivastava, B. Purdue University, West Lafayette, Indiana 47907. Stanislaus, T D S. Valparaiso University, Valparaiso, Indiana 46383. Stefaniak, M. Warsaw University of Technology, Warsaw 00-661, Poland. Stewart, D J. Yale University, New Haven, Connecticut 06520. Strikhanov, M. National Research Nuclear University MEPhI, Moscow 115409, Russia. Stringfellow, B. Purdue University, West Lafayette, Indiana 47907. Suaide, A A P. Universidade de Sao Paulo, Sao Paulo 05314-970, Brazil. Sumbera, M. Nuclear Physics Institute of the CAS, Rez 250 68, Czech Republic. Summa, B. Pennsylvania State University, University Park, Pennsylvania 16802. Sun, X M. Central China Normal University, Wuhan, Hubei 430079. Sun, Y. University of Science and Technology of China, Hefei, Anhui 230026. Sun, Y. Huzhou University, Huzhou, Zhejiang 313000. Surrow, B. Temple University, Philadelphia, Pennsylvania 19122. Svirida, D N. Alikhanov Institute for Theoretical and Experimental Physics NRC "Kurchatov Institute," Moscow 117218, Russia. Szymanski, P. Warsaw University of Technology, Warsaw 00-661, Poland. Tang, A H. Brookhaven National Laboratory, Upton, New York 11973. Tang, Z. University of Science and Technology of China, Hefei, Anhui 230026. Taranenko, A. National Research Nuclear University MEPhI, Moscow 115409, Russia. Tarnowsky, T. Michigan State University, East Lansing, Michigan 48824. Thomas, J H. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Timmins, A R. University of Houston, Houston, Texas 77204. Tlusty, D. Creighton University, Omaha, Nebraska 68178. Tokarev, M. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Tomkiel, C A. Lehigh University, Bethlehem, Pennsylvania 18015. Trentalange, S. University of California, Los Angeles, California 90095. Tribble, R E. Texas A&M University, College Station, Texas 77843. Tribedy, P. Brookhaven National Laboratory, Upton, New York 11973. Tripathy, S K. ELTE Eotvos Lorand University, Budapest H-1117, Hungary. Tsai, O D. University of California, Los Angeles, California 90095. Tu, Z. Brookhaven National Laboratory, Upton, New York 11973. Ullrich, T. Brookhaven National Laboratory, Upton, New York 11973. Underwood, D G. Argonne National Laboratory, Argonne, Illinois 60439. Upsal, I. Brookhaven National Laboratory, Upton, New York 11973. Upsal, I. Shandong University, Qingdao, Shandong 266237. Van Buren, G. Brookhaven National Laboratory, Upton, New York 11973. Vanek, J. Nuclear Physics Institute of the CAS, Rez 250 68, Czech Republic. Vasiliev, A N. NRC "Kurchatov Institute", Institute of High Energy Physics, Protvino 142281, Russia. Vassiliev, I. Frankfurt Institute for Advanced Studies FIAS, Frankfurt 60438, Germany. Videbaek, F. Brookhaven National Laboratory, Upton, New York 11973. Vokal, S. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Voloshin, S A. Wayne State University, Detroit, Michigan 48201. Wang, F. Purdue University, West Lafayette, Indiana 47907. Wang, G. University of California, Los Angeles, California 90095. Wang, J S. Huzhou University, Huzhou, Zhejiang 313000. Wang, P. University of Science and Technology of China, Hefei, Anhui 230026. Wang, Y. Central China Normal University, Wuhan, Hubei 430079. Wang, Y. Tsinghua University, Beijing 100084. Wang, Z. Shandong University, Qingdao, Shandong 266237. Webb, J C. Brookhaven National Laboratory, Upton, New York 11973. Weidenkaff, P C. University of Heidelberg, Heidelberg 69120, Germany. Wen, L. University of California, Los Angeles, California 90095. Westfall, G D. Michigan State University, East Lansing, Michigan 48824. Wieman, H. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Wissink, S W. Indiana University, Bloomington, Indiana 47408. Witt, R. United States Naval Academy, Annapolis, Maryland 21402. Wu, Y. University of California, Riverside, California 92521. Xiao, Z G. Tsinghua University, Beijing 100084. Xie, G. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Xie, W. Purdue University, West Lafayette, Indiana 47907. Xu, H. Huzhou University, Huzhou, Zhejiang 313000. Xu, N. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Xu, Q H. Shandong University, Qingdao, Shandong 266237. Xu, Y F. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Xu, Y. Shandong University, Qingdao, Shandong 266237. Xu, Z. Brookhaven National Laboratory, Upton, New York 11973. Xu, Z. University of California, Los Angeles, California 90095. Yang, C. Shandong University, Qingdao, Shandong 266237. Yang, Q. Shandong University, Qingdao, Shandong 266237. Yang, S. Brookhaven National Laboratory, Upton, New York 11973. Yang, Y. National Cheng Kung University, Tainan 70101. Yang, Z. Central China Normal University, Wuhan, Hubei 430079. Ye, Z. Rice University, Houston, Texas 77251. Ye, Z. University of Illinois at Chicago, Chicago, Illinois 60607. Yi, L. Shandong University, Qingdao, Shandong 266237. Yip, K. Brookhaven National Laboratory, Upton, New York 11973. Zbroszczyk, H. Warsaw University of Technology, Warsaw 00-661, Poland. Zha, W. University of Science and Technology of China, Hefei, Anhui 230026. Zhang, D. Central China Normal University, Wuhan, Hubei 430079. Zhang, S. University of Science and Technology of China, Hefei, Anhui 230026. Zhang, S. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Zhang, X P. Tsinghua University, Beijing 100084. Zhang, Y. University of Science and Technology of China, Hefei, Anhui 230026. Zhang, Y. Central China Normal University, Wuhan, Hubei 430079. Zhang, Z J. National Cheng Kung University, Tainan 70101. Zhang, Z. Brookhaven National Laboratory, Upton, New York 11973. Zhao, J. Purdue University, West Lafayette, Indiana 47907. Zhong, C. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Zhou, C. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Zhu, X. Tsinghua University, Beijing 100084. Zhu, Z. Shandong University, Qingdao, Shandong 266237. Zurek, M. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Zyzak, M. Frankfurt Institute for Advanced Studies FIAS, Frankfurt 60438, Germany.
Keywords: Angular distribution; Angular-modulation; Au+Au collisions; Colliding beam accelerators; Differential cross section; Electron-positron pairs; Invariant mass distribution; Linearly polarized; Matter and antimatters; Photons; Transverse momenta; dept.phy; peer-reviewed